The influence of Bentonite content on the properties of its mixture with Kaolinite - Mohamed M. Salah; Mahmoud S. Hammad; Ayman L. Fayed; Ahmed M. Ebid (Scientific Reports)
Abstract This study investigates the index properties of artificially prepared mixtures of Bentonite and Kaolinite to simulate different types of fine-grained soils with diverse expansive characteristics, with a particular focus on understanding how various index characteristics influence swelling behavior. A series of controlled laboratory tests were conducted to evaluate the specific unit weight, free swell, consistency limits, and compaction parameters. The results show that altering the Bentonite content significantly affects the index properties of the mixtures, which in turn influences their swelling behavior. As the Bentonite content increases, the specific unit weight also increases due to the dense and compact nature of Bentonite. Additionally, the swelling properties of Bentonite cause substantial increases in the free swell and Atterberg limits, highlighting its critical role in controlling swelling potential and plasticity. Conversely, the maximum dry unit weight decreases with increasing Bentonite content due to its high water absorption capacity, which reduces compaction efficiency. These diverse index characteristics, such as free swell, Atterberg limits, and specific unit weight, are found to have a significant impact on the swelling behavior of the mixtures. By adjusting the Bentonite content, these mixtures effectively simulate a range of fine-grained soils with varying swelling potentials. These findings provide valuable insights into the behavior of soils with expansive properties, offering a foundation for optimizing their use in applications like engineered barriers, liners, and foundations, where controlling swelling and plasticity is essential.